If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 2 + -5 = 3 Reorder the terms for easier multiplication: 2x + -5 = 3 Reorder the terms: -5 + 2x = 3 Solving -5 + 2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 3 + 5 2x = 3 + 5 Combine like terms: 3 + 5 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 37-4*7= | | 8a+5b=2b-5a | | 2x+92=9x-13 | | x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a | | d=7h+12 | | 8*a^2+3a-800=0 | | 8*a^2+3a+800=0 | | 2x^3-6x^2+5x+6=0 | | -12h+30=-4h-17 | | 4x=5y+33 | | 15-(5-x)=1 | | 6(1-7k)=40-8k | | 3+2v=-6v+3 | | 2*log(x^2)+log(x-1)=0 | | 2logx^2+logx-1=0 | | 3(p+7)=-33 | | -98=-7(4+b) |